Nanoscopic X-ray fluorescence imaging and quantification of intracellular key-elements in cryofrozen Friedreich’s ataxia fibroblasts - De Samber, Björn (PLoS One, 2018)
Synchrotron radiation based nanoscopic X-ray fluorescence (SR nano-XRF) analysis can visualize trace level elemental distribution in a fully quantitative manner within single cells. However, in-air XRF analysis requires chemical fixation modifying the cell’s chemical composition. Here, we describe first nanoscopic XRF analysis upon cryogenically frozen (-150°C) fibroblasts at the ID16A-NI ‘Nano-imaging’ end-station located at the European Synchrotron Radiation Facility (ESRF) in Grenoble (France). Fibroblast cells were obtained from skin biopsies from control and Friedreich’s ataxia (FRDA) patients. FRDA is an autosomal recessive disorder with dysregulation of iron metabolism as a key feature. By means of the X-ray Fundamental Parameter (FP) method, including absorption correction of the ice layer deposited onto the fibroblasts, background-corrected mass fraction elemental maps of P, S, Cl, K, Ca, Fe and Zn of entire cryofrozen human fibroblasts were obtained. Despite the presence of diffracting microcrystals in the vitreous ice matrix and minor sample radiation damage effects, clusters of iron-rich hot-spots with similar mass fractions were found in the cytoplasm of both control and FRDA fibroblasts. Interestingly, no significant difference in the mean iron concentration was found in the cytoplasm of FRDA fibroblasts, but a significant decrease in zinc concentration. This finding might underscore metal dysregulation, beyond iron, in cells derived from FRDA patients. In conclusion, although currently having slightly increased limits of detection (LODs) compared to non-cryogenic mode, SR based nanoscopic XRF under cryogenic sample conditions largely obliterates the debate on chemical sample preservation and provides a unique tool for trace level elemental imaging in single cells close to their native state with a superior spatial resolution of 20 nm.